AcrDB update: Predicted 3D structures of anti‐CRISPRs in human gut viromes - Khatri, Minal; Shanmugam, N. R. Siva; Zhang, Xinpeng; Patel, Revanth Sai Kumar Reddy; Yin, Yanbin (Protein science, 2025)
Anti‐CRISPR (Acr) proteins play a key role in phage‐host interactions and hold great promise for advancing genome‐editing technologies. However, finding new Acrs has been challenging due to their low sequence similarity. Recent advances in protein structure prediction have opened new pathways for Acr discovery by using 3D structure similarity. This study presents an updated AcrDB, with the following new features not available in other databases: (1) predicted Acrs from human gut virome databases, (2) Acr structures predicted by AlphaFold2, (3) a structural similarity search function to allow users to submit new sequences and structures to search against 3D structures of experimentally known Acrs. The updated AcrDB contains predicted 3D structures of 795 candidate Acrs with structural similarity (TM‐score ≥0.7) to known Acrs supported by at least two of the three non‐sequence similarity‐based tools (TM‐Vec, Foldseek, AcrPred). Among these candidate Acrs, 121 are supported by all three tools. AcrDB also includes 3D structures of 122 experimentally characterized Acr proteins. The 121 most confident candidate Acrs were combined with the 122 known Acrs and clustered into 163 sequence similarity‐based Acr families. The 163 families were further subject to a structure similarity‐based hierarchical clustering, revealing structural similarity between 44 candidate Acr (cAcr) families and 119 known Acr families. The bacterial hosts of these 163 Acr families are mainly from Bacillota, Pseudomonadota, and Bacteroidota, which are all dominant gut bacterial phyla. Many of these 163 Acr families are also co‐localized in Acr operons. All the data and visualization are provided on our website: https://pro.unl.edu/AcrDB.